2016
DOI: 10.1021/acs.joc.6b01618
|View full text |Cite
|
Sign up to set email alerts
|

Chimeric RNA Oligonucleotides Incorporating Triazole-Linked Trinucleotides: Synthesis and Function as mRNA in Cell-Free Translation Reactions

Abstract: A method for the synthesis of chimeric oligonucleotides was developed to incorporate purine nucleobases and multiple triazole linkers in natural, phosphate-linked structures of RNA. A solution-phase synthesis method for triazole-linked RNA oligomers via copper-catalyzed azide-alkyne cycloaddition reaction was optimized and tolerated purine nucleobases and protecting groups for further transformations. Three RNA trinucleotides with 5'-protected hydroxy and 3'-phosphoramidite groups were prepared, and one congen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
(30 reference statements)
0
6
0
Order By: Relevance
“…Previously,w hen we embedded TL RNA in an atural RNA strand as a chimericf orm, we found that t-RNA can form at ransient duplex for translation reactions. [9] In addition, we noted that the translation efficiency with the TL RNA congener was higher than that of natural RNA. Considering the present result of the inferiord uplex formation of TL RNA, we mayu nderstand that the TL RNA oligonucleotides can be particularly suitable for applications that requires hort-lived, transient duplexes.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Previously,w hen we embedded TL RNA in an atural RNA strand as a chimericf orm, we found that t-RNA can form at ransient duplex for translation reactions. [9] In addition, we noted that the translation efficiency with the TL RNA congener was higher than that of natural RNA. Considering the present result of the inferiord uplex formation of TL RNA, we mayu nderstand that the TL RNA oligonucleotides can be particularly suitable for applications that requires hort-lived, transient duplexes.…”
Section: Discussionmentioning
confidence: 93%
“…[7] After the development of our duplex-forming triazole-linked DNA analogues ( TL DNA), [5,8] we developedt riazole-linked RNA analogues ( TL RNA) with 2'-hydroxy groups installed on pseudonucleosides. Although duplex formations were indicated in the form of am ixed oligomer of a TL RNA-RNA chimera, [9] poor synthetic protocols precluded us from synthesizing long oligonucleotides, mainly due to insufficient efficiency of the elongation processes. [10] We herein report the synthesiso faduplexforming oligonucleotide of TL RNA.…”
Section: Introductionmentioning
confidence: 99%
“…This procedure was later adapted by other research groups and further modified, [113,114] and even combined with traditional phosphoramidite approaches. [17,115,116] The triazole linkage is generally stable and can be designed to be of similar length as the native phosphodiester bond (Figure 9B-E). [117] Figure 8.…”
Section: Application Of Azide-modified Oligonucleotidesmentioning
confidence: 99%
“…In the case of synthetic elements that have an artificial sugar–phosphate backbone, a DNA plasmid possessing a few triazole linkages instead of phosphodiester linkages has been accepted as a template for natural mRNA transcription in both E. coli and human cells. Also, short stretches of RNA possess a few triazole linkages, that have a different design from the aforementioned triazole linkagerecognized as an mRNA in reconstructed E. coli translation systemalthough single nucleotide misreading occurred at the triazole-linked codon . Phosphorothioate linkage-containing RNA has been proven to raise the mRNA activity in the prokaryotic translation systems in vitro .…”
mentioning
confidence: 99%
“…11−13 Also, short stretches of RNA possess a few triazole linkages, that have a different design from the aforementioned triazole linkagerecognized as an mRNA in reconstructed E. coli translation systemalthough single nucleotide misreading occurred at the triazole-linked codon. 14 Phosphorothioate linkage-containing RNA has been proven to raise the mRNA activity in the prokaryotic translation systems in vitro. 15 Furthermore, with respect to elements that have synthetic sugar parts, a four consecutive codon composed of synthetic elements that has six-membered sugar rings was transliterated into natural DNA, 16 while short stretches of DNA containing 4′-thionucleotides could be transcribed into natural RNA in mammalian cells.…”
mentioning
confidence: 99%